Analysis of the dependence of the number of allocated systems of lineaments on the grouping interval width - Khodorovskyi, A. J.; Аpostolov, A.А. (Reports of the National Academy of Sciences of Ukraine, 2014)
The numbers of the systems of lineaments, as well as cracks and breaks, allocated by separate authors, are different considerably, which interferes the subsequent quantitative processing of a field of lineaments. The reasons for such situation were not analyzed. The carried out researches have shown that the width of the interval of grouping of the lineaments influences significantly the number of systems of lineaments allocated on the graph of distribution of their stretch azimuths. It is established, that the dependence of the number of allocated systems of lineaments on the width of the interval of grouping is described by a hyperbola with the coefficient of correlation R2 = 0.948.